Strategi Zakat Fitrah untuk Meningkatkan Kesejahteraan Masyarakat di Desa Cempaka Nuban, Lampung Timur - Bella Permata Sari; Imelda Deva Kirana; Rahmad Riski Wahyudi; Rama Harfi Ferdinan; Siti Zulaikha (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to analyze the management strategy of zakat fitrah in improving community welfare in Cempaka Nuban Village, East Lampung. The research used a descriptive qualitative approach with data collection techniques through observation and interviews with zakat committee members and beneficiaries. The findings indicate that zakat fitrah management is still traditional in both collection and distribution processes. The zakat is distributed to three main groups: the poor, the needy, and those in the cause of Allah (fisabilillah). Awareness strategies are carried out through religious talks during Ramadan, which have proven effective in increasing muzakki compliance. Zakat fitrah plays a significant role in alleviating the economic burden of beneficiaries and enhancing social solidarity during the festive season. The study concludes that zakat fitrah has the potential to be a strategic instrument for improving rural community welfare if managed systematically and with community involvement.